Notes to Philosophy 167: Class 6 -- Galileo's Two New Sciences: Local Natural Motion -- Part 16. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: The Evidential Difficulties as of 1651: A Recap -- Galileo's Place in the History of Mechanics -- Galileo's Contribution to Scientific Method -- Philosophical Disputes Over Two New Sciences -- Issues We Must Face and Our Approach to Them -- Select Sources.; Generally corresponds to the video segment: Class 6, Part 16.